CYANOTIC HEART DISEASE: AN OVERVIEW OF TETRALOGY OF FALLOT - Laksono, Gerardo; Tahalele, Paul L (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
Tetralogy of Fallot (TOF) is the most common cyanotic heart disease with anomalies consist of: ventricular septal defect (VSD), overriding aorta, pulmonary stenosis and hypertrophic of the right ventricular. It also has various anomalies type such as TOF with absent pulmonary valve, TOF with pulmonary atresia, TOF with atrioventricular septal defect, TOF with coronary artery anomalies, etc which will be discussed in detail. Proper diagnosis is required when dealing with the TOF continue with radiological examination. Adequate history taking and correct physical examination are necessary in dealing with congenital heart defects, especially TOF case. In this overview, we also discuss about the comprehensive management, from tet spell management, palliative management of TOF that required shunt with various technique, and surgical total corrective of TOF with many approach such as transannular accompany with right ventriculotomy or transatrial with transpulmonary or beating heart surgery technique to prevent reperfusion injury complication.